PROBLEME ECONOMICE GLOBALE: ÎMPĂDURIREA ZONELOR CU RISC DE SECETĂ DIN ROMÂNIA - USM ADMIN (Studia Universitatis Moldaviae: Stiinte Umanistice, 2008)
Taking into account the specificity of the forestation problem, it is possible to observe certain particularities that are not to be neglected at both the initial stage and that of assessing effectiveness indices. One of the particularities mentioned above is the necessity to determine the optimal moment for zonal forestation, as related economic activities may be underway at either the middle or just the start of their development stage. Another factor is related to the necessity to consider the specific forms the indices may assume in the case of zonal forestation as compared to the current situation. Indices of effectiveness are based upon direct incompatibility with the former owing to production structure changes, production infrastructure, climate, population professional activities, etc. The necessity of zonal (and not only zonal) forestation is evident and is intuitively supported by the whole nation. However, as practice shows, certain forest areas in private possession are burnt out or otherwise destroyed, which constitutes a violation of the law. This situation could be avoided by applying economic and administrative levers as well as by creating complexes of the forestry-industrial processing-marketing character. Forestry should be maintained on a stable level within the system of the growing prices for respective raw materials.